Public Solicitation and The Canadian Media: Two Cases of Living Liver Donation, Two Different Stories - Marcon, Alessandro R (Transplant Direct, 2019)
BACKGROUND: . Two stories of public solicitation for living liver donors received substantial Canadian media attention in 2015: The Wagner family, with twin toddlers, each needing transplants, and Eugene Melnyk, wealthy owner of a professional hockey team. This study compared the print media coverage of these 2 stories to understand how public solicitation was portrayed and whether coverage differed depending on the individual making the plea. METHODS. We conducted a content analysis on 155 relevant Canadian newspaper articles published between January 1, 2015 and December 31, 2016. Articles were analyzed for their description of public solicitation, benefits and issues associated with public solicitation, and overall tone with respect to public solicitation. RESULTS. The foregrounding of public solicitation and associated ethical issues featured heavily in articles focused on Melnyk but were largely absent when discussing the Wagner family. The fairness of Melnyk's solicitation was the most prominent ethical issue raised. Laws and policies surrounding public solicitation also featured in the Melnyk story but not in articles focused on the Wagners. Public solicitation was portrayed more negatively in the Melnyk articles, but overall, was portrayed positively in relation to both Melnyk and the Wagner family. CONCLUSIONS. Public solicitation was generally portrayed as a positive phenomenon in Canadian print media, yet there were stark differences in how these cases were presented. The Wagner story was largely portrayed as a human-interest piece about a family in dire circumstances, whereas Melnyk's wealth, status, and influence raised questions of the fairness of his transplant.